Economic growth, economic performance and welfare in south Asia - Jha, Raghbendra (Palgrave Macmillan, 2005)
Nineteen papers written by academics and other public policy analysts consider the economic prospects of South Asia, which has in recent years led the world in terms of economic growth. Editor Jha (executive director, Australia South Asia Research Centre, Australian National U.) has organized the proceedings around the themes of macroeconomic performance; emerging economic challenges; trade, industrial, and financial sector reform; foreign perceptions of and foreign investment in South Asia; and poverty alleviation. Naturally, much of the material is devoted to the economics of India, being the powerhouse of the region, but there is also coverage of Bangladesh, Nepal, Sri Lanka, and Pakistan.